Respuesta :
Answer:
1/2
Step-by-step explanation:
myltiply 2/3 by 2/2 and then subtact 1/6 from the new 4/6 to give you 3/6. it simplifies to 1/2
The correct value will be "[tex]\frac{1}{2}[/tex]".
The given expression is:
→ [tex]\frac{2}{3}+(-\frac{1}{6} )[/tex]
By opening the bracket, we get
→ [tex]\frac{2}{3} -\frac{1}{6}[/tex]
By taking L.C.M, we get
→ [tex]\frac{4-1}{6}[/tex]
→ [tex]\frac{3}{6}[/tex]
→ [tex]\frac{1}{2}[/tex]
Thus the above solution is appropriate.
Learn more:
https://brainly.com/question/11457028?referrer=searchResults